Islam dalam Oposisi Demokratis di Indonesia - Priyono, AE (Studia Islamika, 1995)
This article is a review of the book "Democracy and Diffusion: Transnational Lesson Drawing among Indonesian Pro-Democracy Actors" by Uhlin unders (87 Lund Political Studies, Department of Political Science, Lund University, 1995).Anders Uhlin publication of a book which was originally a dissertation at the University of Lund, Sweden, is motivated by the noisy atmosphere of a critique of theories of political regime transitions. Uhlin himself considered that the transition theories suffer from a bias towards the view as if democracy is only relevant in any political environment, and because it always implies the need for democratization of the regime transformation. Broader issues concerning democratization of civil-society, which often does not imply a transition regime, tend to be ignored by the theories of transition. That's why he said, the transition to democracy should be analyzed in conjunction with developments in the wider community.DOI: 10.15408/sdi.v2i4.826